Effect of two types of tillage and N fertilization on cotton root biomass in the water shed of Ouri-Yori (Municipality of Matéri) - OGA, AMOUR; IGUE, ATTANDA MOUINOU; SAIDOU, ALIOU; OLODO, E.; GAISER, THOMAS (My University, 2015)
Management of soil fertility in particular of the tropical degraded ferruginous soils is a key factor for attaining potential crop yield. An experiment was conducted to investigate the effect of different systems of tillage and nitrogen fertilizer on root biomass of cotton (Gossypium hirsutum), plant height and leaf area index. The experiment was laid out in a split plot design with tillage systems conventional tillage (CT) and reduced tillage (RT), fertilizer rates (0; 60 and 120 Kg N/ha) and mulching Crop mulching (M) and no mulching (NM). Our results showed that at 30, 60 and 120 days after sowing, tillage systems had a significant effect (P<0.001; P<0.01and P<0.05) on cotton root biomass at 0 - 10 cm; 10 - 20 cm and 30 - 40 cm depth. A significant effect of tillage system was also recorded on plant height at 21, 42 and 63 days after sowing. The highest average plant height (121 ±1.3 cm) was obtained with the conventional tillage. However, tillage system did not show a significant (P>0.05) effect on the leaf area index. The effect of nitrogen fertilizer was significant (P<0.01 and P<0.05) on root biomass at 90 and 120 days after sowing. The interaction between tillage system and nitrogen fertilization dose significantly (P<0.01 and P<0.001) affected the root biomass. However, the highest number of roots (15.453±3.23g/plant), plant height and leaf area index was recorded in the conventional tillage with the fertilizer rate of 120 kg N/ha. In addition, tillage system and nitrogen fertilization had a significant effect on the date of flowering of cotton plants. It can be concluded from the study that CT and nitrogen fertilizer boosted root growth, leaf area index and plant height of cotton.
Keywords: Soil tillage; nitrogen fertilizer; tropical ferruginous soil; cotton roots